2017
DOI: 10.3390/ijms18010128
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Search for Circulating Tumor Cells in Patients Undergoing Prostate Brachytherapy for Clinically Nonmetastatic Prostate Cancer

Abstract: Despite the absence of local prostate cancer recurrence, some patients develop distant metastases after prostate brachytherapy. We evaluate whether prostate brachytherapy procedures have a potential risk for hematogenous spillage of prostate cancer cells. Fifty-nine patients who were undergoing high-dose-rate (HDR) or low-dose-rate (LDR) brachytherapy participated in this prospective study. Thirty patients with high-risk or locally advanced cancer were treated with HDR brachytherapy after neoadjuvant androgen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…that surgical manipulation can promote the dissemination of tumor cells into the circulation (5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…that surgical manipulation can promote the dissemination of tumor cells into the circulation (5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…CTCs are released from the primary tumor into the bloodstream and have the potential to spread to distant sites and develop into micro-metastatic deposits (4). Furthermore, surgical manipulation could promote the dissemination of tumor cells into the circulation (5)(6)(7). Prognosis improvement is expected with the no-touch isolation technique (NTIT) due to preventing surgical manipulation.…”
mentioning
confidence: 99%
“…To the best of our knowledge, there are no reports describing CTCs changes following primary external beam RT. A recent study from Japan, reported elevation in CTC numbers after brachytherapy for prostate cancer [26]. However, this was attributable to surgical manipulation of the gland.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue also covered studies on seminal plasma biomarkers [ 35 ], improved PET contrast between osteolytic and osteoblastic bone metastatic lesions with fasting [ 36 ] and the impact of the blood collection tube and storage time on CTC-mRNA (AR-V7) analysis [ 37 ]. Two clinical studies on different biomarkers for prostate brachytherapy [ 38 , 39 ] complete the large number of publications.…”
Section: Overviewmentioning
confidence: 99%
“…The last two studies of this Special issue present data on patients receiving prostate brachytherapy [ 38 , 39 ]. In the sixth study from Germany by PD Ecke et al [ 38 ] PSA, PSA density and other clinical data were evaluated before and after brachytherapy with external beam radiation in 79 high-risk PCa patients treated between 2009 and 2016.…”
Section: Brachytherapymentioning
confidence: 99%